(untitled) (Interdisciplinary Studies Journal, 2024)
This research aims to understand the current challenges of Public Policies in Vocational and Technological Education in the construction of critical knowledge. In this context, as a problem, we seek to analyze the extent to which historical factors impact the training offered by this modality today, specifically regarding teacher education in the professional and technological perspective. Historically, vocational education has been present in Brazil since the colonial period, with milestones that divided the modality, essentially catering to the working class, contributing to a dualistic education that separates teaching quality between the rich and the poor. In the 2000s, the objectives of this modality underwent changes. The current Vocational and Technological Education (VET) was implemented in 2008 under Law 11,892, which transformed the CEFETs into the current Federal Institutes, with an education system that spans from high school to postgraduate level. Despite the new objectives to qualify and prepare students for the job market with the consolidation of a critical education that makes the student autonomous and aware of their social reality, when observing teacher education in VET, it is notable that many teachers begin their teaching careers without proper qualifications, assuming different responsibilities, preparing teaching plans for different educational levels, and facing long working hours, among other functions. This is a bibliographical research of articles and books that address the researched topic, with a qualitative approach. The results indicate that, although initial and ongoing training is required by law for teachers entering the Federal Institutes and they have the right to participate in initial training, such as a second degree or a lato sensu postgraduate course, it is evident that, even after 15 years since the creation of the Federal Institutes, there is still a lack of public educational policies that prepare teachers for a vertically integrated education system, from high school to postgraduate level. This contributes to a traditional and reproductive education that benefits capital and hinders the development of critical teacher and, subsequently, student education.